Safe delivery: Concept Paper - Mudege, Abigail Thandiwe; Kasu, Christine, Mary; Mugadza, Gladys; Kapfunde, Abigail; Haruzicishe, Clara (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Safe delivery is important in reducing maternal and neonatal morbidity and mortality rates worldwide. Studies have shown that there is no clear definition of what safe delivery.